Review: Adaptation of Beneficial Propionibacteria, Lactobacilli, and Bifidobacteria Improves Tolerance Toward Technological and Digestive Stresses - Gaucher, Floriane; Bonnassie, Sylvie; Rabah, Houem; Marchand, Pierre; Blanc, Philippe; Jeantet, Romain; Jan, Gwénaël (Frontiers in Microbiology, 2019)
Beneficial bacteria including Propionibacteria, Lactobacilli and Bifidobacteria, may be used for many industrial applications, as probiotics or a starters, or both. They should be stabilized under a dry form in order to decrease transportation and storage costs. Bacteria can be dried by freeze-drying or by spray-drying; these two processes are stressful for bacteria. To be a good starter and keep probiotic properties, bacteria have to survive following drying, during storage and during digestion. Survival during storage is a key challenge, that the industrial sector should tackle. Bacteria have many molecular mechanisms of adaptation, which can be induced during sub lethal stress, and which to increased survival of bacteria upon lethal stress. In this review, we outline the main molecular adaptation mechanisms present in Propionibacteria, Lactobacilli and Bifidobacteria. Different mechanisms and molecules involved in stress sensing, molecular adaptation at the cell wall, membrane and cytoplasm levels are reviewed synthetically. We describe then the impact of the adaptation mechanisms on technological and digestive stresses tolerance. These data should help finding the best treatments, which can reinforce bacteria during drying, storage and digestion.